1999
DOI: 10.1046/j.1365-313x.1999.00515.x
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling secretion and tip growth in lily pollen tubes: evidence for the role of calcium in exocytosis

Abstract: SummaryCytoplasmic calcium concentration ([Ca 2+ ] i ) and extracellular calcium (Ca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 38 publications
3
71
0
Order By: Relevance
“…These two events are thus as much as 1408 out of phase, and yet it is a paradigm in plant and animal cells (Battey et al, 1999), including pollen tubes (Roy et al, 1999;Camacho and Malhó , 2003), that Ca 2+ stimulates secretion. How do we explain this apparent lack of correlation between Ca 2+ and secretion?…”
Section: Oscillation Of the Intracellular [Ca 2+ ] Does Not Regulate mentioning
confidence: 99%
See 1 more Smart Citation
“…These two events are thus as much as 1408 out of phase, and yet it is a paradigm in plant and animal cells (Battey et al, 1999), including pollen tubes (Roy et al, 1999;Camacho and Malhó , 2003), that Ca 2+ stimulates secretion. How do we explain this apparent lack of correlation between Ca 2+ and secretion?…”
Section: Oscillation Of the Intracellular [Ca 2+ ] Does Not Regulate mentioning
confidence: 99%
“…This essential ion (Brewbaker and Kwack, 1963) forms a steep tipfocused gradient at the extreme apex of the tube (Rathore et al, 1991;Miller et al, 1992;Malhó et al, 1994;Pierson et al, 1994;Roy et al, 1999) where it may stimulate exocytosis (Battey et al, 1999;Roy et al, 1999). Further studies have revealed that the Ca 2+ gradient oscillates in magnitude with the same period as growth rate; however, it follows the increase in growth rate by 10 to 408 (Messerli et al, 2000;Cá rdenas et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Alternative energyproducing machinery may be induced to some degree upon a Ca 2+ -CaM signaling deficiency that allows FM endocytic uptake, in accordance with an up-regulated PDC bypass as the energy source for FM internalization (Parton et al, 2001;Gass et al, 2005). In contrast, accumulating evidence has confirmed that the dissipation of the tip-focused Ca 2+ gradient may contribute to the decrease in vesicle accumulation and fusion (Roy et al, 1999). We found a gradual decrease in AcPase activity and a differential display of secretory pathway-related proteins (spots 12 and 57), providing direct evidence for reduced exocytic vesicular trafficking in TFP-treated pollen tubes.…”
Section: Proteins Involved In Cellular Structure/secretory Pathway Asmentioning
confidence: 99%
“…It is well accepted that Ca 2+ has a profound effect on the oriented transport of vesicles toward the cell wall in the extreme pollen tube tip (Roy et al, 1999). Rapid turnover of the intracellular pool of UDPG has been reported during pollen tube elongation, which attests to the metabolic specialization of pollen tubes for rapid wall synthesis (Gibeaut, 2000).…”
Section: Proteins Involved In Polysaccharide Synthesis As the Tertiarmentioning
confidence: 99%
“…A number of Ca 2+ -regulated cellular activities, such as cytoskeleton dynamics, exocytosis, and endocytosis, are directly or indirectly involved in the regulation of pollen tube growth (Roy et al, 1999;Hwang et al, 2005;Helling et al, 2006;Konrad et al, 2011). Based on the observation that Ca 2+ is known to regulate the activity of ion channels in many other physiological processes, Ca 2+ and its downstream components are assumed to play crucial roles in modulating ion channel activity during pollen tube growth.…”
Section: Introductionmentioning
confidence: 99%